Vitamin D, intact parathyroid hormone, and bone mineral density in postmenopausal women (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2024)
Background: Osteoporosis and vitamin D deficiency (VDD) are growing concerns for the elderly population, especially postmenopausal women worldwide. The association between osteoporosis and VDD among Bangladeshi postmenopausal women was not adequately evaluated.Objective: To assess the association between VDD, intact parathyroid hormone (iPTH) status, and bone mineral density (BMD) status among postmenopausal Bangladeshi women.Methods: This single-center, cross-sectional study included 60 postmenopausal women. A pre-designed case record form was used to record baseline demographic variables. BMD was assessed using dual-energy X-ray absorptiometry on eligible patients who met the inclusion and exclusion criteria, where T-scores indicating normal (> -1), osteopenia (-1 to -2.5), or osteoporosis (< -2.5) based on lumbar spine (LS) and femoral neck (FN) measurements. Vitamin D was categorized as deficient (